Analysis of speech development in preschool children with autism spectrum disorders - Y.O. Korobina; O.A. Ivanova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2022)
The features of mental and speech development of younger schoolchildren with autism spectrum disorders (ASD) have been widely studied by various sciences and at their interface. However, they are still poorly understood in preschool children having the same diagnosis. Using a psycholinguistic approach, this article reviews and summarizes the findings of both Russian and foreign researchers on speech development in preschool children with ASD symptoms. Their most essential characteristics of speech development were revealed. Conditions that determine their progress in verbal communication and the communicative and pragmatic functions of their speech were identified and analyzed. The level of speech development in preschoolers attending a specialized kindergarten at Kazan Federal University for children with ASD was described.